Pemanfaatan Sistem Informasi untuk Pengelolaan Medik dan Jasa Kesehatan di Klinik - Hendarti, Henny; Anggita, Seplita; Wina, Wina (Bina Nusantara University, 2008)
Article presented an information system development which can facilitate the doctors and nurses at clinic in managingoutpatient and reporting data quickly, accurately, and effectively. Before using a computerized system, all data recording wasstill done conventionally using paper media. The research method used was an analysis and designing method, interviews,library research, and field study as to do an observation. The analysis and designing method, which was proposed, used anobject-oriented concept and presented through notation of Unified Modeling Language (UML). The research results showedthat a clinic needs a new system which can facilitate the doctors and nurses in processing operational data, such as medicalrecord data and other data relating to the outpatient. It can be concluded that with the presence of the information system, itis expected that it can facilitate the information needs by using a computerized system.Keywords: system utillty, information system, medical management, clinic